(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Despite the success achieved in the treatment of AD, the disease tends to progress, being one of the causes of the development of pulmonary hypertension (PH) and chronic cor pulmonale (CPS). Mortality in AD reaches 250000 people per year. One of the main causes of disability and mortality is the involvement of the heart and blood vessels, which often determines the severity and prognosis of AD.